Desarrollo y producción del primer capítulo de la novela visual Tecnólisis - Ayala Koo, Rodrigo Abelardo (2023)
This report provides an account of the development of Technolysis’ first chapter, a cyberpunk visual novel available in Spanish and English. Visual novels are a narrative medium—originated in Japan—in which the user progresses by reading blocks of text and making choices. Narration is accompanied by sprites of the characters and illustrations that depict the events in the story. Music and sound effects are also used in order to complement the user’s experience. The developers set on writing and producing the necessary creative materials to develop Technolysis’ first chapter through a cyberpunk aesthetic.